Structure, biomass, and secondary production of benthic macroinvertebrates in subtropical Andean rivers - Hankel, Guillermo Eduardo (2023)
Secondary production is the formation of heterotrophic biomass across time, which integrates several important ecological processes that affect the life of organisms, populations, communities and ecosystems, but its study has poor developed in South America. The objectives of this work were to describe the diversity of benthic macroinvertebrate assemblages in terms of abundance and biomass, and to quantify their secondary production for the first time in Andean rivers. A quantitative sampling scheme was implemented, using a Surber sampler, in three forested streams. Physicalchemical variables, nutrients, organic matter and chlorophyll were measured also. The macroinvertebrates were separated and identified mostly at the species level. Each taxon was assigned to a functional feeding group. Secondary production was estimated for 38 taxa, mostly Diptera, Trichoptera, Coleoptera, and Ephemeroptera. The annual production varied from 3769 to 13916 mg dry mass m-2 y-1. Most abundant taxa were also those with higher production, dominated by Ephemeroptera (Baetidae), Trichoptera (Hydropsychidae) and Diptera (Chironomidae and Simuliidae). Density, biomass, and production of collectors and predators were much higher than the other feeding groups. We expect that our results will be useful to evaluate the effects on stream functioning produced by global warming and other anthropogenic disturbances in our region.